Increased Vascularity in the Neonatal versus Adult Meniscus: Evaluation with Magnetic Resonance Imaging. (December 2021) - Lin, Kenneth M.; Gadinsky, Naomi E.; Klinger, Craig E.; Dyke, Jonathan P.; Rodeo, Scott A.; Green, Daniel W.; Fabricant, Peter D.; Helfet, David L.; Shea, Kevin G.; Lazaro, Lionel E.
Objective . Quantification of meniscus vascularity has been limited with previous techniques, and minimal data exist describing differential vascular zones in the skeletally immature meniscus. The objective of this study is to use quantitative contrast-enhanced magnetic resonance imaging (MRI) to compare meniscal vascularity in neonatal specimens with adults. We hypothesized that the developing meniscus has greater and more uniform vascularity throughout all zones. Design . Ten fresh-frozen human cadaveric knees (5 neonatal, age 0-6 months; 5 adult, 34-67 years) underwent gadolinium-enhanced MRI using an established vascularity quantification protocol. Regions of interest corresponding to peripheral and central zones of the meniscus were identified on pre-contrast coronal images, and signal enhancement within the same regions (normalized against background tissue) was compared between pre- and post-contrast images. Results . The medial and lateral menisci had similar distribution of perfusion (45.8% ± 8.1% medial vs. 54.2% ± 8.1% lateral in neonatal knees; 50.6% ± 11.3% medial vs. 49.4% ± 11.3% lateral in adult knees, P = 0.47). Increased perfusion was demonstrated in the periphery compared with the central zone (2.3:1 in neonatal knees and 3.25:1 in adult knees, P = 0.31). Neonatal specimens demonstrated 6.0-fold greater overall post-contrast meniscal signal enhancement compared with adults ( P < 0.0001), with the 0-month specimen demonstrating the greatest proportional signal enhancement. Conclusions . While blood flow to the periphery is greater than to central zones in all menisci, younger menisci receive proportionally greater overall blood flow compared to adults, including to the central zone, suggesting that the immature meniscus is a more biologically active tissue than its adult counterpart.